2017
DOI: 10.1073/pnas.1620722114
|View full text |Cite
|
Sign up to set email alerts
|

Impact of backbone fluorination on nanoscale morphology and excitonic coupling in polythiophenes

Abstract: Fluorination represents an important strategy in developing highperformance conjugated polymers for photovoltaic applications. Here, we use regioregular poly(3-ethylhexylthiophene) (P3EHT) and poly(3-ethylhexyl-4-fluorothiophene) (F-P3EHT) as simplified model materials, using single-molecule/aggregate spectroscopy and molecular dynamic simulations, to elucidate the impacts of backbone fluorination on morphology and excitonic coupling on the molecular scale. Despite its high regioregularity, regioregular P3EHT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…19 F NMR only afforded a single peak, again suggestive of very high degrees of backbone regioregularity. In agreement with our earlier studies, [38] all fluorinated poly mers were less soluble than their nonfluorinated analogues and required processing from hot chlorinated solvents like chlo robenzene or 1,2dichlorobenzene. The molecular weights, as measured by gel permeation chromatography (GPC) in either hot chlorobenzene (P3OTbFP3OT and P3OTaltFP3OT or hot 1,2,4trichlorobenzene (FP3OT), of all fluorinated poly mers were similar ( Table 1).…”
Section: Synthesissupporting
confidence: 92%
“…19 F NMR only afforded a single peak, again suggestive of very high degrees of backbone regioregularity. In agreement with our earlier studies, [38] all fluorinated poly mers were less soluble than their nonfluorinated analogues and required processing from hot chlorinated solvents like chlo robenzene or 1,2dichlorobenzene. The molecular weights, as measured by gel permeation chromatography (GPC) in either hot chlorobenzene (P3OTbFP3OT and P3OTaltFP3OT or hot 1,2,4trichlorobenzene (FP3OT), of all fluorinated poly mers were similar ( Table 1).…”
Section: Synthesissupporting
confidence: 92%
“…The large blueshift up to 35 nm in absorption features might result from the molecular conformation, as absorption spectra have been shown to be depended on the molecular conformation. [27,28] Thus, we confirmed that the temperature effect can induce molecular conformation variations of conjugated polymers. The conformation variations can affect the solution-state aggregation and polymer crystallization in the film-formation process, [13,29,30] which are well supported by the following experiments and simulations.…”
supporting
confidence: 73%
“…were conducted in order to evaluate the proposed program. F-P3EHT is a fluorinated P3EHT that is reported to have an extended structure in chloroform [8]. As another example, MD simulations of polystyrene in THF and water were also conducted.…”
Section: Simulations Of Poly (3-ethylhexylthiophene) (P3eht) and Pmentioning
confidence: 99%
“…The obtained files were implemented in the 2018 version of Gromacs to perform the 20-ns MD simulation. The simulation conditions were set as suggested by Hua et al [8]. That is, P3EHT, and F-P3EHT were set in a 14.4-nm cubic box filled with chloroform, and the periodic boundary condition was applied.…”
Section: Simulationmentioning
confidence: 99%